Linking Land Administration Domain Model and BIM environment for 3D digital cadastre in multi-storey buildings. (May 2021) - Atazadeh, Behnam; Olfat, Hamed; Rajabifard, Abbas; Kalantari, Mohsen; Shojaei, Davood; Marjani, Afshin Mesbah
Abstract: 3D digital cadastral systems intend to provide a fully-integrated 3D view of legal boundaries and rights, restrictions and responsibilities (RRR) in multi-storey properties, which is aligned with the physical reality. Our cognitive understanding of legal boundaries and RRR information is more communicable when we link it to our visual perception of the real world. However, there is a knowledge gap in logical relationships between legal and physical views as most of the existing approaches that integrate 3D legal and physical dimensions have been mainly proposed on a conceptual level. The main argument of this study is that the multi-dimensional nature of BIM provides the ability to extend this environment with concepts defined in Land Administration Domain Model (LADM) for the purpose of 3D digital cadastre in buildings. Therefore, this study investigated how an open BIM-based data model, known as Industry Foundation Classes (IFC), can be extended with LADM data elements to support integration of legal and physical views. This will create a linkage between LADM and BIM environment, which would subsequently provide a better cognitive understanding of legal spaces. Highlights: The multi-dimensional nature of BIM provides the ability to extend this environment with concepts defined in LADM. This study aims to create a linkage between LADM and BIM environment. Having a unified 3D data environment will reduce current issues in finding legal boundaries in buildings. Integrating legal and physical dimensions of buildings should be based on international standards.